(untitled) (Journal of Forensic Medicine & Toxicology, 2016)
Traditional lectures are one of the oldest forms of teaching in large group size in medical colleges even today. However, didactic lectures are considered ineffective in affecting learning outcomes of knowledgeretention, student satisfaction, syntheses and elaboration of knowledge. Two main problems encountered in lecture format of teaching, is poor student interaction and low attention span. Consequently, new strategies to transform didactic lectures in to effective lectures are emerging due to recent advances in our understanding of cognitive science on learning and memory. In the present study, new interactive methods were applied to increase student participation and improve their attention span in large group teaching.